2023
DOI: 10.1097/ccm.0000000000006067
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Incidence and Outcomes of Cardiac Arrest Occurring in Swedish ICUs

Benjamin Flam,
Mikael Andersson Franko,
Markus B. Skrifvars
et al.

Abstract: Objective: To determine temporal trends in the incidence of cardiac arrest occurring in the ICU (ICU-CA) and its associated long-term mortality. Design: Retrospective observational study. Setting: Swedish ICUs, between 2011 and 2017. Patients: Adult patients (≥18 yr old) recorded in the Swedish Intensive Care Registry (SIR). Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Early after admission, it is possible that there is a false believe that giving patients initial adequate treatment might improve status and that could be waited for. Another recent study by our group has explored IHCA occurring in the ICU, 18 even if the main focus was not causes of ICU-CA that study found that most were postoperative and re-arrest in prehospital or in-hospital cardiac arrests.…”
Section: Discussionmentioning
confidence: 99%
“…Early after admission, it is possible that there is a false believe that giving patients initial adequate treatment might improve status and that could be waited for. Another recent study by our group has explored IHCA occurring in the ICU, 18 even if the main focus was not causes of ICU-CA that study found that most were postoperative and re-arrest in prehospital or in-hospital cardiac arrests.…”
Section: Discussionmentioning
confidence: 99%